Analisis Kontrol Kualitas Produk Ikan Dori Goreng Tepung di PT. Aerofood Indonesia Unit Surabaya - Alfian Pramesthi Dwi Viandini; Lilis Sulandari (Intellektika : Jurnal Ilmiah Mahasiswa, 2025)
Quality control is a process to ensure that the products or services produced meet the standards or specifications that have been set. Dori fish (Zeus Faber) is a perishable food, so it requires proper handling and processing to maintain its quality. This study aims to determine the quality control of flour fried dori fish products at PT. Aerofood Indonesia Surabaya unit which includes the preparation, processing and storage stages with qualitative descriptive research methods through observation and interviews conducted with 5 resource persons. The results of the study show that 1). The implementation of the quality control system at PT. Aerofood Indonesia Surabaya Unit at the preparation stage including equipment, thawing, cutting, bathering and breading has 100% met the standards and for marinating has met 50% of the standards 2). At the processing stage in the frying process, 50% has met the standard and for cooling using a blast chiller , 50% has met the standard 3). At the final storage stage the product includes portioning and final storage has 100% met the standards. It can be concluded that quality control affects the process of preparation, processing and storage of flour fried dori fish products so that the quality of the product is maintained. This shows the importance of quality control in the food industry